The Urgency of Stunting Policy Management Based on Local Knowledge in Malang Regency - Kurniawan, Faizal; Maksum, Ali; Anas, Muhammad; Yusainy, Cleoputri (Universitas Muhammadiyah Malang, 2024)
In the Malang Regency region, the issue of stunting is pressing. According to statistics showing the high rate of stunting in Malang Regency, a stunting management strategy must be put into place right away. To date, the issue has been whether policies at the upstream level address all the factors necessary to combat stunting. This study talks about how urgent municipal policies are, particularly for managing stunting. It should be mentioned that government policies currently in place are focused on improving and regulating food security, food quality, and program socialization. Additionally, both targeted and delicate treatments are a manifestation of the prevention of stunting. The heath industry performs specific interventions. The phenomenology of Malang Regency's stunting prevention strategies is revealed by this study. According to the study's findings, there are a number of issues that require immediate attention, particularly those that are local in nature, like local education on the marriage readiness index, particularly in areas with a high incidence of young marriage, like Tajinan sub-district. The health sector, as well as other connected sectors, must be involved in the regional follow-up to the village level of policies and regulations that are in place at the federal level. Due to the community's increased knowledge of the value of a balanced diet and the readiness of parents at marriageable age, the community-based coping system needs to be improved once more. Localized coping strategies will undoubtedly.